2019
DOI: 10.1109/tmtt.2019.2951773
|View full text |Cite
|
Sign up to set email alerts
|

System EVM Characterization and Coverage Area Estimation of 5G Directive mmW Links

Abstract: RF performance of 5G new radio (NR) millimeter wave (mmW) system will be characterized over-the-air (OTA) in 3GPP 5G NR performance and type approval testing. Total system Error Vector Magnitude (EVM) performance has not been standardized in 3GPP since mobile and base stations are certified separately. In this paper, we extend the OTA measured system EVM concept to cover EVM performance testing with beam steering for 5G mmW radio link. We show that the OTA measured system EVM inside of an electromagnetic compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 17 publications
0
28
0
Order By: Relevance
“…The measured EVMs in the main lobe are improved from 8.3% and 8.9% to 4.9% and 4.8% with DPD. The achievable EVM values are limited also by other RF nonidealities, such as IQ-imbalance and phase noise [41]. The measured main-lobe efficiencies are above η EIRP = 22% and total radiated efficiencies are better than η TRP = 2.8% with DPD.…”
Section: B Radiated Linearization Performancementioning
confidence: 92%
“…The measured EVMs in the main lobe are improved from 8.3% and 8.9% to 4.9% and 4.8% with DPD. The achievable EVM values are limited also by other RF nonidealities, such as IQ-imbalance and phase noise [41]. The measured main-lobe efficiencies are above η EIRP = 22% and total radiated efficiencies are better than η TRP = 2.8% with DPD.…”
Section: B Radiated Linearization Performancementioning
confidence: 92%
“…Also, a few new OTA parameters have been investigated for better describing the performance of the AAU systems. For instance, Leinonen et al demonstrated the use of the EVM-based beamwidth of the radiated beam for characterizing the coverage of the mmWave BSs [166]. A beam EIRP (BEIRP) was proposed to reflect a certain beam radiated transmit power in multibeam mmWave AAU system [167].…”
Section: B Rf Characteristic Testingmentioning
confidence: 99%
“…That is due to difficulty of reliable measurement interfaces when even very small parasitics have a major impact on the result and antennas need to be either integrated on-chip or otherwise with very small parasitic load to RF electronics. Fortunately, with advanced OTA methods it is possible to evaluate link performance and even noise figure, other RF parameters, and maximum link ranges based on Error Vector Magnitude (EVM) or other means for the whole system [55]. Of course, extracting details from the whole system, including both receiver and transmitter, is not straightforward and information of separate parts from stand-alone probe measurements is highly preferred.…”
Section: System Demonstrationsmentioning
confidence: 99%